Transnational Education and Soft Diplomacy: The Experience of Malaysian History Students at Universitas Andalas, 1985–1997 - Yani, Wahyu Suri (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This article examines Malaysian students’ mobility to Universitas Andalas (Unand) in Padang from 1985 to 1997 as a case of transnational education and soft diplomacy in Southeast Asia. Drawing from archives, official reports, and oral histories, it argues that studying at Unand was not merely a pragmatic response to Malaysia’s limited domestic opportunities but also a manifestation of cross-border intellectual exchange. The study reveals that Malaysian students negotiated academic and cultural identities within a “third space” (Bhabha, 1994), adapting to new historiographical traditions and social environments through networks, collaboration, and lecturer support. Their theses engaged with Indonesian historiography, Minangkabau history, and the interconnected development of Malay and Indonesian nationalism. This article demonstrates that transnational education at Unand functioned as a form of soft diplomacy, fostering cultural affinities, intellectual bridges, and long-term bilateral understanding between Malaysia and Indonesia.